Accuracy of a Flash Glucose Monitoring System in Diabetic Dogs. (18th June 2016) - Corradini, S.; Pilosio, B.; Dondi, F.; Linari, G.; Testa, S.; Brugnoli, F.; Gianella, P.; Pietra, M.; Fracassi, F.
Abstract : Background: A novel flash glucose monitoring system (FGMS) (FreeStyle Libre, Abbott, UK) was recently developed for humans. It continuously measures the interstitial glucose (IG) concentrations for 14 days. Objectives: To assess the clinical and analytical accuracy of the FGMS in diabetic dogs. Animals: Ten client‐owned diabetic dogs on insulin treatment. Methods: Prospective and observational study. The FGMS was placed on the neck for up to 14 days. During the 1st–2nd, 6–7th, and 13–14th days from application, the IG measurements were compared with the plasma (EDTA) glucose (PG) concentrations analyzed by a reference hexokinase based method. Results: The application and the use of the FGMS were apparently painless, easy, and well tolerated by all dogs. Mild erythema at the site of the application was found in 5/10 dogs at the end of the wearing period. A good correlation between IG and PG concentrations (rho = 0.94; P < .001) was found. The FGMS was 93, 99, and 99% accurate at low, normal, and high blood glucose concentrations. Mean ± standard deviation difference from the reference method was 2.3 ± 46.8 mg/dL. Conclusion and clinical importance: The FGMS is easy to use and is accurate for IG glucose measurement in diabetic dogs.